Different Human–Dog Interactions in Early Agricultural Societies of China, Revealed by Coprolite - Zhang, Yunan; Sun, Guoping; Zhang, Dong; Yang, Xiaoyan; Wu, Xiaohong (Frontiers in Earth Science, 2021)
Dogs served in a variety of capacities in prehistory. After their domestication in Paleolithic hunter-gatherer societies, the emergence of agriculture shifted their partnerships with people. However, the associations between dogs and early farmers are not readily visible in the archaeological record. In the present study, dog coprolites uncovered from two groups of early agricultural societies in China during the Neolithic Age, the early rice agricultural site of Tianluoshan in the lower Yangtze River, and three early millet-rice mixed agricultural sites of Shuangdun, Yuhuicun and Houtieying along the middle Huai River, were examined based on the comparisons of lipid and palynological results to reveal different relationships of dogs and humans in subsistence strategies. The Tianluoshan dog showed a plant-dominated diet with higher contents of plant sterols and fatty alcohols with longer chain lengths. Dogs may have lived on foraging or been provisioned with refuse for the cleanness purpose. On the contrary, dogs from the sites of Shuangdun, Yuhuicun and Houtieying showed a meat-dominated diet with higher proportions of animal sterols and short-chain fatty alcohols. It most probably referred to their assistance in hunting and thus being provisioned with meat. Furthermore, activity areas of dogs also reflect different deployment strategies and agricultural systems, evidenced by pollen spectra from the coprolites. Dogs at Tianluoshan mostly appeared in the wetland area, in correspondence with the labor-consuming rice cultivation as the main targeted resource, showing their role in daily agricultural activities. On the other hand, high concentrations of pollen from forest and grassland revealed that hunting dogs played a regular role in the early millet-rice mixed farming societies, probably related to the importance of hunting activities in the daily subsistence.